Will Mobile Application Technology Help Retail Merchandising ? Breakthrough Innovation by FMCG Companies - Ravi, Shilpa Sarvani; Bhagat, Shikha (Indian Journal of Marketing, 2020)
For the retail business to run successfully and to improve sales, the critical component is to display its products and services in a visually appealing manner. Retail merchandising assists the retailers to attract shoppers and influence their purchase. Often, the merchandising updates are not escalated up the hierarchy ladder as they are much dynamic and spontaneous in nature. Top manufacturing FMCG companies like HUL, ITC, etc. took up this challenge of modern trade merchandising by maintaining manpower in organized retail stores to tap the cutting edge of competitive advantage. The key challenges of these merchandisers include – maintaining overall shelf health, frequency and consistency of restocking, tracking the competition actions in the store, eliminating the conflicting signages, remove broken displays, and display compliances. These FMCG companies have adopted a breakthrough innovation of mobile applications to overcome these challenges. This study is novel and investigated the sales performance improvement through mobile application technology. The research was conducted in two parts. Part 1 included structural interviews (one-on-one) with retail store managers and FMCG sales representatives. The results disclosed eight major attributes as store trend, competition update, personnel management, stock availability, demand creation, in-store visibility, new products launch and promo packs, and share of shelf to improve sales performance. Part 2 examined the significance of these eight factors through quantitative study by considering FMCG merchandisers as respondents. The study identified that competition update, stock availability, personnel management, in-store visibility, and share of shelf were significant factors that impacted sales performance in retail merchandising by utilizing mobile technology applications.